Effect of Rice Bran Oil on Cholesterol and Triglycerides in Patients with Central Obesity in the Working Area Health Centers Mattombong Pinrang - Syakur, Umar; Sirajuddin, Saifuddin; Rahmadani, Rahmadani (Journal of Community Health Provision, 2025)
Poor metabolic effects on blood pressure, cholesterol, triglycerides, and insulin resistance are caused by being overweight or obese. The study's objective was to evaluate how rice bran oil affected the central obese patient's changes in triglycerides and cholesterol. The study was a quasi-experiment with a control group and a non-randomized pre- and post-test.  Purposive sampling was used to choose the sample, which included 46 individuals split into two groups.  For 15 days, the treatment group received 25 milliliters of rice bran oil each day, while the control group did not receive any.  Triglyceride and cholesterol levels were assessed both before and after the intervention.  Using the SPSS software, the data were examined by comparing the lipid profile results before and after a particular intervention using the Wilcoxon paired t test and comparing the treatment between groups using the Man Whithney independent t test. The study's findings show that the intervention group's cholesterol levels significantly changed, with an average drop of 13.39 mg/dl and an average increase of 8.39 mg/dl in the control group. The difference between the two groups is not statistically significant (p=0.144).  This indicates that the intervention group and the control group are identical. There is an insignificant difference between the intervention group and control group (p=0.001), with the intervention group experiencing a considerable drop in triglyceride levels (mean decrease of 70.95 mg/dl) and the control group experiencing an increase of 10.73 mg/dl.  This indicates that the intervention group and the control group are different.